Pengaruh Substitusi Tepung Ampas Tahu Pada Egg RollTerhadap Kadar Protein Dan Daya Terima - Triatmaja, Muhayat; , Pramudya Kurnia, STP, M.Agr; , Rusdin Rauf, STP, MP (2016)
Introduction: The nutritional problem in Indonesia at this time are overnutrition and malutrition. The prevalence of malnutrition in Indonesia reaches 13,9%, cause of malnutrition is a lack of energy an protein. Protein content in tofu pulp is high enough that is 23,39%, however utilization of tofu is not optimal and can pollute the environment. Egg roll manufacture products industry has been widely spread in Indonesia. The utilization of tofu pulp powder as a substitution of egg roll can help to reduce malutrition and help egg roll manufacture products industry as a modification of making egg roll. Objective: the objective of this research is to know the effect of tofu pulp powder substitution on egg roll towards protein content and sensory acceptence. Research Method: The type of research is experimental. The research design is randomized complete block design those are three treatments and one control with two repetitions. The amount of substitutions in tofu pulp are 0%, 20%, 30% and 40%. Protein content is obtained by using micro Kejldahl and sensory acceptence is obtained by a test with 30 panelists. Statictics test by using Anova than continued by Duncan test. Result: The result from Anova showed that p value of the egg roll sensory acceptences towards color 0,01, aroma 0,37, taste 0,03, texture 0,95, and totality 0,47. Conclusion: There is a difference or effect of tofu pulp powder substitution in tofu egg roll towards protein content, color, and taste, however there is no effect on aroma, texture, and on the whole. Suggestion: Further research about the production of egg roll by using tofu pulp powder substitution could also be conducted to get the right color, aroma, taste, texture and totality of egg roll, also regard the process or the way of processing tofu pulp powder in order to eliminate unpleasant smell and a bitter taste.